Alburnoides diclensis (Actinopterygii: Cyprinidae), a new species of cyprinid fish from the upper Tigris River, Turkey - Turan, Davut; Bektaş, Yusuf; Kaya, Cüneyt; Bayçelebi̇ Esra (Zootaxa, 2016)
Alburnoides diclensis sp. n. is described from the Tigris River drainages (Persian Gulf basin) in southeastern Anatolia, Turkey. It is distinguished by a combination of the following characters (none unique to the species): a poorly developed ventral keel between pelvic and anal fins, completely scaled or rarely without one scale in front of anus; head short (length 24–27% SL), its upper profile markedly convex on level of nostril; mouth terminal, with marked chin; lips equal to or upper lip slightly longer than lower lip; snout with rounded tip, its length equal to or greater than eye diameter but smaller than interorbital distance; body moderately deep (depth at dorsal-fin origin 25–30% SL); anal-fin depth 1.2–1.4, mean 1.3 times in HL; 48–53 lateral-line scales, 12½–15½ branched anal-fin rays; 41–42 total vertebrae, comprising 20–21 abdominal and 20–21 caudal vertebrae.